Structured Quiz for Teaching of CVM Stages to the Undergraduate Orthodontic Students - Azeem, Muhammad; Ul Haq, Arfan; Awaisi, Zubair Hassan; Ehsan, Ambreen Afzal (Orthodontic Journal of Nepal, 2019)
Introduction: There are several methods of teaching out of which didactic lectures and student centered lecturesa re commonly practiced all over the world in medical and dental schools. The aim of the study was to find out the impact of introducing structured quiz as a method for teaching of cervical vertebral maturation (CVM) stages to the undergraduate orthodontic students. Materials & Method: Current study was conducted on 30 undergraduate orthodontic students of final year. Duration of Study was 2018-19. Initial MCQs test was followed by the lecture and hands-on on quiz pattern and this was followed by the MCQs final-tests. The scores were calculated and presented in form of mean. Student paired t test was applied to compare the initial-test quiz scores with final-test quiz scores. Result: Results showed significant differences between initial-test and final-test which showed a significant improvement. Conclusion: The introduction of structured quiz as a method for teaching of cervical vertebral maturation (CVM) stages resulted in significant improvement in the knowledge of undergraduate orthodontic students.